Утилізація електровакуумного скла відпрацьованих кінескопів в силікатній суміші для виготовлення силікатної цегли - Завгородня, Наталія Ігорівна; Півоваров, Олександр Андрійович; Носенко, Олександр Васильвич (НТУ "ХПІ", 2016)
Визначена можливість заміни 10 мас. % кварцового піску склобоєм електровакуумного скла в силікатній суміші для виготовлення силікатної цегли. Наведена методика експерименту. Визначено вологопоглинання та щільність експериментальних зразків силікатної цегли. Випробувано експериментальні зразки на зміну межі міцності при стиску та щільність від тривалості ізотермічної витримки. Досягнуто скорочення на 0,5 години часу автоклавування силікатної суміші за рахунок часткової заміни кварцового піску склобоєм електровакуумного скла.

The analysis of a state of affairs is provided in world practice on use of electrovacuum glass of the fulfilled kinescopes as a cullet. A definite purpose of research on application of a cullet of barium-strontic and lead glass in production of silicate mix for production of a silicate brick. The experiment technique with the detailed characteristic of raw materials is given. Moisture absorption, weight and density of experimental samples of a silicate brick are defined. Experimental samples are tested for change of border of durability at compression and density from duration of isothermal endurance. Reduction for 0,5 hours of duration of autoclave processing of silicate mix due to partial replacement of quartz sand with a cullet of electrovacuum glass of the fulfilled television kinescopes and computer monitors is reached.
Utilization in silicate mix for production of the silicate brick of electrovacuum glass of the fulfilled kinescopes
Keywords: межа міцності; щільність; водопоглинання; durability border; density; moisture absorption